2004
DOI: 10.1140/epjb/e2004-00301-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a protein complex network

Abstract: The budding yeast Saccharomyces cerevisiae is the first eukaryote whose genome has been completely sequenced. It is also the first eukaryotic cell whose proteome (the set of all proteins) and interactome (the network of all mutual interactions between proteins) has been analyzed. In this paper we study the structure of the yeast protein complex network in which weighted edges between complexes represent the number of shared proteins. It is found that the network of protein complexes is a small world network wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 26 publications
0
32
0
1
Order By: Relevance
“…Similar approaches have been presented in previous works [24,25], with older datasets [14,15]. For instance, Mashaghi et al [24] used a similar approach, but we consider all three kinds of networks, while Ref. [24] dealt only with the bipartite network and the complex-mode projection.…”
Section: Methodsmentioning
confidence: 99%
“…Similar approaches have been presented in previous works [24,25], with older datasets [14,15]. For instance, Mashaghi et al [24] used a similar approach, but we consider all three kinds of networks, while Ref. [24] dealt only with the bipartite network and the complex-mode projection.…”
Section: Methodsmentioning
confidence: 99%
“…The results are shown in Figs. 7,4,5,6 where it is clearly shown that the power-law degree distribution is robust with respect to variations in all these parameters.…”
mentioning
confidence: 99%
“…Scale-free networks are important in a range of topics from ecology and evolution theory [3], to protein folding and neural networks [4][5][6], technological and scientific networks [7], social sciences [8], economics [9,10] and cascade analysis [11].…”
mentioning
confidence: 99%
“…Recent research along this topic has been largely focused on the modelling of epidemics [4][5][6][7][8][9][10] and its interplay with biological interactions, which has yielded many valuable and interesting results [11,12]. Some of these models studied have attracted the attention of epidemiologists [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%